Modulation by endothelin-1 of spontaneous activity and membrane currents of atrioventricular node myocytes from the rabbit heart. - Stéphanie C Choisy; Hongwei Cheng; Godfrey L Smith; Andrew F James; Jules C Hancox (PLoS ONE)
Background The atrioventricular node (AVN) is a key component of the cardiac pacemaker-conduction system. Although it is known that receptors for the peptide hormone endothelin-1 (ET-1) are expressed in the AVN, there is very little information available on the modulatory effects of ET-1 on AVN electrophysiology. This study characterises for the first time acute modulatory effects of ET-1 on AVN cellular electrophysiology. Methods Electrophysiological experiments were conducted in which recordings were made from rabbit isolated AVN cells at 35-37°C using the whole-cell patch clamp recording technique. Results Application of ET-1 (10 nM) to spontaneously active AVN cells led rapidly (within ~13 s) to membrane potential hyperpolarisation and cessation of spontaneous action potentials (APs). This effect was prevented by pre-application of the ET(A) receptor inhibitor BQ-123 (1 µM) and was not mimicked by the ET(B) receptor agonist IRL-1620 (300 nM). In whole-cell voltage-clamp experiments, ET-1 partially inhibited L-type calcium current (I(Ca,L)) and rapid delayed rectifier K(+) current (I(Kr)), whilst it transiently activated the hyperpolarisation-activated current (I(f)) at voltages negative to the pacemaking range, and activated an inwardly rectifying current that was inhibited by both tertiapin-Q (300 nM) and Ba(2+) ions (2 mM); each of these effects was sensitive to ET(A) receptor inhibition. In cells exposed to tertiapin-Q, ET-1 application did not produce membrane potential hyperpolarisation or immediate cessation of spontaneous activity; instead, there was a progressive decline in AP amplitude and depolarisation of maximum diastolic potential. Conclusions Acutely applied ET-1 exerts a direct modulatory effect on AVN cell electrophysiology. The dominant effect of ET-1 in this study was activation of a tertiapin-Q sensitive inwardly rectifying K(+) current via ET(A) receptors, which led rapidly to cell quiescence.